PENGUATAN HARMONISASI SOSIAL MELALUI PENDAMPINGAN PENGEMBANGAN KURIKULUM PAI RESPONSIF TERHADAP KEBERAGAMAN - Khasanah, Uswatun; Purwoko, Purwoko; Chasanah, Uswatun (Jurnal Indonesia Mengabdi, 2025)
This Community Partnership Program (PKM) aims to strengthen social harmony through participatory and collaborative mentoring in developing an Islamic Education (PAI) curriculum that is responsive to diversity. The program was initiated based on the limited integration of religious moderation, tolerance (tasamuh), and appreciation of pluralism within the existing PAI curriculum structure in educational institutions. The method employed a participatory and gacor slot collaborative mentoring approach implemented through five stages: needs assessment, conceptual reinforcement workshop, curriculum development mentoring, limited implementation trial, and evaluation and reflection. The results demonstrate significant reconstruction of the PAI curriculum, particularly in the reformulation of learning outcomes, enrichment of contextual and inclusive materials, application of dialogical and participatory learning strategies, and development of value-based attitude assessment instruments. In addition to producing a more inclusive and context-sensitive curriculum document, the program enhanced teachers’ professional capacity to develop and refine curricula in a reflective and sustainable manner. The implementation of the revised curriculum showed increased student engagement and the creation of a more dialogical and harmonious classroom atmosphere. Therefore, mentoring in developing a diversity-responsive PAI curriculum can serve as an effective strategy for strengthening social harmony in educational settings and reinforcing the transformative role of religious education in fostering inclusive and civic-minded character development.